Racism in Brazil: The State Autonomy of Mitigating Social Inequalitys (Global Journal of Human-Social Science, 2023)
The purpose of this article is to discuss the human rights of Afro-descendants and it s evolution in Brazil especially with regard to the historical political and social structure The characterization of information from the colonial period to current Brazil is analyzed making considerations about the contrast of racism and the rights conquered among Afro-descendant individuals Within this concept the work proposes to present a critical study with the purpose of exposing discrimination and social inequality within society and how those supported by State law aim at effective public policies to combat in an attempt to mitigate or end these problems that affect the development of about 56 2 of the Brazilian population
Keywords: afro-descendants rights state racism